Avaliação de estratégias de visualização em dados climáticos: uma análise através da perspectiva do usuário - Fagundes, Vinícius Antônio Campos (2017)
Meteorological data as well as their predictions are increasingly present now a days. It is very common , for example, see weather forecasts on TV news or alerts to specific locations on a possible natural disaster about to occur, such as floods, hurricanes, among others. For the analysis and dissemination of this information, visualization techniques are used so that these data are presented to the public in an understandable way. But such climate information isn’t always clearly presented, making it difficult to understand. This work of dissertation proposal presents a study about the most used forms of representation of these visualization techniques, trying to identify the main techniques and how to use them in most of the types of meteorological data. Thus, a systematic mapping was performed in the area in order to identify them, as well as their forms of representation, 2D, 3D or even interactive. Finally, an evaluation of use with volunteer users is proposed, seeking to identify how well this type of information is understood when disseminating information about a specific climate data.